Pollution Load Capacity Analysis of BOD, COD, and TSS in Karang Mumus River, Samarinda - Vita Pramaningsih; Slamet Suprayogi; Ignasius Loyola Setyawan Purnama (Indonesian Journal of Chemistry, 2020)
The Rivers in Indonesia often accommodate pollution from all community activities. This happened due to a large number of people who use watersheds for living. One of those rivers is the Karang Mumus River in Samarinda City, East Kalimantan. This study aims to analyze the capacity of the Karang Mumus River pollution load in segments 2, 3 and 4. The analysis model used in this study was the QUAL2Kw and ArcGIS models. The former used to calculate the capacity of river pollution and the latter used to determine land use. The results of the QUAL2Kw Model analysis shown that the capacity of the BOD was exceeded in all segments, COD was exceeded in all segments except segment 3. The entire segment had an allocation of sectoral pollution load originated from domestic activities. This study concluded that the dominant land use of settlements was one of the main causes of this problem.